SUPLEMENTASI MANNANASE DALAM RANSUM RENDAH PROTEIN TERHADAP PRODUKSI DAN KUALITAS TELUR AYAM ISA BROWN (Mannanase Supplementation in the Low-Protein Diet Fed to Isa Brown Hen on Egg Production and Quality) - Rendy setiawan; Sumiati yuyum; Adrizal muhammad (Buletin Ilmu Makanan Ternak, 2017)
The objective of the study was to evaluate whether mannanase supplementation in the low protein diet fed to laying hens from 31 to 45 weeks of age would improve egg production and quality. The experiment was designed into completely randomized designed with 2 treatments and 20 replicates. Two hundred and thirty six 31-week old ISA brown hens were distributed at random to individual cage. Two experimental diets containing 15% protein without (0%) or with mannanase supplementation (0,05% [72,5 MU/kg product Elanco, Animal Health IN, USA] ) were assigned to cages, so each treatment had 20 replicates with 5- 6 birds per treatment. Feed intake, egg production (hen day and egg mass), egg weight, and feed conversion ratio (FCR) were recorded every week in the period of 31-35 weeks and 42 to 45 weeks of age. On Week 34 and 45, eggs were collected for egg quality analysis (albumen height, haugh unit, yolk color, shell thickness, shell strength and shell weight). Data were subjected to one way of ANOVA (with 20 replicates per treatment). The results showed that mannanase supplementation had had no effects on performance parameters (feed intake, egg production, egg weidht, and FCR) measured at 31 to 35 weeks of age, but had significant effect (P <0,05) on daily feed intake, and FCR on 42 to 45 weeks of age. With regard to egg quality, only egg shell weight was improved by mannanase supplementation. In conclusion, dietary supplementation to low protein diet could improve feed conversion and egg shell quality.